Busy Book Media Improves Fine Motor Skills in Early Childhood: Buku Aktivitas Interaktif Meningkatkan Keterampilan Motorik Halus pada Anak Usia Dini - Handika, Edy Arizul; IFFATUR ROCMAH, LULUK (Universitas Muhammadiyah Sidoarjo, 2025)
General background: Fine motor development is a crucial aspect of early childhood education as it supports children’s cognitive, social, and language growth. Specific background: However, many preschool learning environments still rely heavily on worksheets, providing limited stimulation for fine motor practice. Knowledge gap: Limited studies in Indonesian early childhood settings have examined the systematic use of interactive learning media such as Busy Book to optimize motor skills. Aims: This study aimed to improve the fine motor skills of 4–5-year-old children through the application of Busy Book media in classroom learning. Results: Using Classroom Action Research with the Kemmis & Taggart model involving 14 children, findings showed significant improvement across two cycles. In Cycle I, imitating achieved 64.29%, finger movement 58.93%, and inserting fabric 64.29%. In Cycle II, these indicators increased to 82.14%, 94.64%, and 78.57% respectively, showing substantial progress. Novelty: This study highlights that Busy Book provides an engaging, hands-on, and child-friendly tool that enhances children’s interest and motivation while simultaneously strengthening fine motor skills. Implications: Teachers and parents are encouraged to integrate Busy Book into school and home learning to provide richer stimulation for children’s early development.6 Highlights: Busy Book significantly increased fine motor skills within two learning cycles. The media stimulated children’s motivation and engagement in learning. Practical implications for teachers and parents in early education settings.9 Keywords: Fine Motor Skills; Early Childhood; Busy Book; Classroom Action Research; Learning Media